The impact of emergent virtual leadership competencies on team effectiveness. Issue 2 (25th February 2014) - Ziek, Paul; Smulowitz, Stacy
Abstract : Purpose: – The research on virtual team leadership does well to describe the skills that are needed to guide and direct effective teams. However, what is presupposed in the previous research is that virtual teams have assigned leaders. That is, leaders were either management, appointed by management or were chosen by the team itself. Yet in today's global economy not all virtual teams have assigned leaders, instead many virtual team leaders emerge on their own to direct the group's actions. The purpose of this paper is to examine which emergent leadership competencies most impact virtual team effectiveness. Design/methodology/approach: – This is a mixed method study where both a participant survey and content analysis of actual participant messages are used to determine the competencies of emergent virtual team leaders. The research participants for the current study were required to work in assigned teams on organizational case analyses. At the end of each case, teams presented their solutions in the form of final recommendations designed to fix the problem present in the case. Findings: – Results indicate that not only do leaders emerge in virtual teams, but in most cases multiple leaders emerge. Results also show that the model that best describes team effectiveness includes the competencies of asking questions, cognitive and creative ability and vision setting. Originality/value: – The contribution of the current study is that it extends the research on emergent virtual team leadership by introducing the idea that this type of leadership is often a collective action among individuals. It also advances a model of emergent virtual team leadership as a practice of communication. The better emergent virtual team leaders are at communicating to team members the more effective the team will be in completing tasks and projects, which in turn can lead to a more effectively functioning business unit.